(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Golf game is competitive and it has attracted many participants due to its unique features. In the many features, kinetics of golf swing was analyzed to improve one’s performance level. The present study examined the center of mass (COM) of a recreational golfer during a phase from address to backswing top for two different golf clubs. Kinematic data were evaluated. The results indicated that there were some differences in COM between two different golf clubs.